Multi-modal piezoelectric energy harvester - Lim, Jiunn Hao (2017)
Nowadays, there is a rising demand for energy harvesting from ambient environment to conduct Structural Health Monitoring (SHM) for civil and building structures. In order to achieve continuous self-powered wireless sensing, piezoelectric materials have been used to harness electrical energy from vibration energy using piezoelectric energy harvester. Due to its flexibility, Macro Fibre Composite (MFC) has established its useful application as piezoelectric material attached to a cantilever beam. However, linear harvester has a single resonant peak in the frequency domain and suffers from narrow operational bandwidth. The target of this project is to achieve multiple peaks with wider bandwidth. In this project, effort has been put in for the design with three peaks. This project addresses this issue by developing innovative multi-modal piezoelectric energy harvester. The proposed design consists of a main cantilever beam with three smaller beams attached to it. Voltage and power outputs are recorded and analysed and MFC is used in the tests. ANSYS simulation was conducted beforehand to obtain the system parameters for the tests. The voltage output shows the improvement in the bandwidth compared to linear harvester. The tests are carried out under acceleration of 0.075g, 0.1g and 0.15g. Comparison between the two designs is presented.